Float, fly, then sink: wetland plant seed buoyancy is lost after internal dispersal by waterbirds - María J. Navarro-Ramos; Andy J. Green; Robin de Vries; Casper H. A. van Leeuwen (Hydrobiologia, 2024)
Seed dispersal distance is an important indicator of how well a plant species can cope with environmental changes. Seeds of wetland plants are primarily dispersed by hydrochory (floating on the water surface) or endozoochory (ingestion and egestion by animals). However, both mechanisms can also be combined (diplochory), which increases dispersal distances. In wetlands, seeds often float on the water surface before ingestion and transport by animals, such as waterbirds. Here, we consider what happens next after endozoochory and test whether seeds dispersed inside waterbirds can then continue to disperse by hydrochory. We experimentally assessed the buoyancy capacity of 41 wetland plant species for 14 weeks before and after simulated passage through avian digestive systems. This revealed that (1) seeds of plants previously assigned a hydrochory dispersal syndrome floated longer than those from other syndromes, but with considerable overlap; (2) fully aquatic and shoreline plant species had seeds with stronger buoyancy than terrestrial plants; and (3) digestive processes negatively affected seed buoyancy capacity for all plant species, which included wetland species with a typical hydrochory syndrome. The capacity for hydrochory is more limited after endozoochory than beforehand, with strong implications for the effectiveness of seed dispersal.